Cryptanalysis of a generalized anonymous buyer-seller watermarking protocol of IWDW 2004 - Goi, , BM; Phan, , RCW; Siddiqi,, MU (2005)
In this paper, we analyze the security of a generalized anonymous buyer-seller watermarking protocol recently proposed by Choi and Park at IWDW 2004. We prove that it has not met the designers' intended security criteria by showing that an attacker can actually: (1) discover the unique buyer's watermark which was chosen by the watermark certificate center (WCC), and (2) decrypt the encrypted watermarked digital content without any extra cost. Also, it is surprising to note that when designing their protocol, the designers did not take into consideration the conspiracy attacks.